2023
DOI: 10.1186/s13054-023-04715-z
|View full text |Cite
|
Sign up to set email alerts
|

Dysnatremia at ICU admission and functional outcome of cardiac arrest: insights from four randomised controlled trials

Jean Baptiste Lascarrou,
Cyrielle Ermel,
Alain Cariou
et al.

Abstract: Purpose To evaluate the potential association between early dysnatremia and 6-month functional outcome after cardiac arrest. Methods We pooled data from four randomised clinical trials in post-cardiac-arrest patients admitted to the ICU with coma after stable return of spontaneous circulation (ROSC). Admission natremia was categorised as normal (135–145 mmol/L), low, or high. We analysed associations between natremia category and Cerebral Performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…It is inefficient to predict a patient’s prognosis with a CDI diagnosis in that the relevant guideline recommends predicting prognosis at least 72 h after the return to normothermia [ 2 ]. Additionally, hyponatremia was more prevalent than hypernatremia after ROSC [ 6 ], complicating the diagnosis of CDI, as hypotonic polyuria is not typically suspected, making water deprivation tests or desmopressin administration tests challenging. However, previous research has indicated that high SOsm and low UOsm are useful for predicting CDI [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is inefficient to predict a patient’s prognosis with a CDI diagnosis in that the relevant guideline recommends predicting prognosis at least 72 h after the return to normothermia [ 2 ]. Additionally, hyponatremia was more prevalent than hypernatremia after ROSC [ 6 ], complicating the diagnosis of CDI, as hypotonic polyuria is not typically suspected, making water deprivation tests or desmopressin administration tests challenging. However, previous research has indicated that high SOsm and low UOsm are useful for predicting CDI [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%